Bacteria and their toxins tamed for immunotherapy - Adkins, Irena; Holubova, Jana; Kosova, Martina; Sadilkova, Lenka (Current pharmaceutical biotechnology, 2012)
Bacterial toxins share the ability to enter host cells to target various intracellular proteins and to modulate host immune responses. Over the last 20 years, toxins and their mutated variants, as well as live attenuated bacteria, have been exploited for vaccination and immunotherapy of various infectious, malignant and autoimmune diseases. The ability of Bordetella pertussis adenylate cyclase toxin to translocate its adenylate cyclase domain across the host cell membrane, as well as the pathways of intracellular trafficking of Bacillus anthracis lethal and edema toxins, Shigella dysenteriae shiga toxin or Escherichia coli shiga-like toxin, have been repeatedly exploited for the delivery of antigenic epitopes into host cells and for stimulation of antigen-specific T cell responses. Similarly, E. coli α-hemolysin, or effector proteins of Yersinia and Salmonella secreted by the type III secretion systems, were used to facilitate the delivery of fused heterologous proteins or peptides for antigenic presentation. Vibrio cholerae cholera toxin, E. coli heat-labile enterotoxin, B. pertussis pertussis toxin or the Cry1A protein of Bacillus thuringiensis have shown a great potential to act as adjuvants and to stimulate mucosal as well as systemic immune responses. The immunotherapeutic potential of some toxins, like Clostridium perfringens perfringolysin O, Streptococcus intermedius intermedilysin, or Streptococcus pneumoniae pneumolysin needs to be evaluated further. The Bordetella adenylate cyclase toxoid used as a vaccine delivery tool, or Corynebacterium diphtheriae diphtheria toxin and Pseudomonas aeruginosa exotoxin A-based immunotoxins, are currently in various phases of clinical trials for cancer immunotherapy, as are some antigen-delivering Salmonella and Listeria monocytogenes strains.
Keywords: Bacterial Toxins; Immunotherapy; Neoplasms; Antigens; bakteriální toxiny; imunoterapie; zvířata; Humans; antigeny; nádory; lidé; Animals